Charter and Revised Ordinances of the City of Eureka (Eureka, CA: Standard Print, 1905), 251. Penal Ordinances, Ordinance No. 55— Prohibiting the Carrying of Concealed Weapons, §§ 1-4. Approved November 6, 1878 - (:unkn) unknown (General Publisher, 1878)
Prohibited the concealed carry of any pistol, dirk, or dangerous or deadly weapon. Violators guilty of a misdemeanor, punishable by fine not exceeding one hundred dollars, or imprisonment not exceeding ten days, or both.
--
Keywords: CARRY - CONCEALED